Improving the Image of Women in Social Media Based on Gender Justice for Teenagers - Rini Fidiyani; Eko Mukminto; Irawaty Irawaty; Widhiyanto Widhiyanto; Rahayu Fery Anitasari; Edward Michael Simangunsong; Hafidz Daffa; Samuel Adi Nugroho (Jurnal Abdimas, 2024)
The social media network has become one of the most favored digital technology platforms for information and entertainment among the public today. However, in social media practices, women often appear as objects that are sexualized or commodified commercially. According to a survey by wearesocial.com and Hootsuite, most internet users in Indonesia fall into the categories of teenagers and young adults. Building upon the results of this survey, community service focuses on the age group of 13 to 18 years old who are currently studying at a Senior High School (SMA). This community service initiative occurs at a Public Senior High School in Semarang City, Central Java. The activity involves the socialization and mentoring of 100 students (50 males and 50 females). This activity influences the perspectives and behaviors of teenagers towards the portrayal of women on social media, leading to an average score change from 39 (before socialization) to an increased average of 89 (after socialization and mentoring), which represents a significant increase.